Fine Mapping of the Wheat Leaf Rust Resistance Gene LrLC10 (Lr13) and Validation of Its Co-segregation Markers - Qiu, Lina; Wang, Huifang; Li, Yinghui; Wang, Weidong; Liu, Yujia; Mu, Junyi; Geng, Miaomiao; Guo, Weilong; Hu, Zhaorong; Ma, Jun; Sun, Qixin; Xie, Chaojie (Frontiers in Plant Science, 2020)
Wheat leaf rust, caused by the fungus Puccinia triticina Eriks. (Pt), is a destructive disease found throughout common wheat production areas worldwide. At its adult stage, wheat cultivar Liaochun10 is resistant to leaf rust and the gene for that resistance has been mapped on chromosome 2BS. It was designated LrLC10 and is the same gene as catalogued gene Lr13 by pedigree analysis and allelism test. We fine-mapped it using recessive class analysis of the homozygous susceptible F2 plants derived from crosses using Liaochun10 as the resistant, male parent. Taking advantage of the re-sequencing data of Liaochun10 and its counterpart susceptible parent, we converted nucleotide polymorphisms in the LrLC10 interval between the resistant and susceptible parents into molecular markers to saturate the LrLC10 genetic linkage map. Four indel markers were added in the 1.65 cM map of LrLC10 flanked by markers CAUT163 and Lseq22. Thirty-two recombinants were identified by those two markers from the 984 F2 homozygous susceptible plants and were further genotyped with additional ten markers. LrLC10 was finally placed in a 314.3 kb region on the Chinese Spring reference sequence (RefSeq v1.0) that contains three high confidence genes: TraesCS2B01G182800, TraesCS2B01G182900, and TraesCS2B01G183000. Sequence analysis showed several variations in TraesCS2B01G182800 and TraesCS2B01G183000 between resistant and susceptible parents. One KASP marker and an indel marker were designed based on the differences in those two genes, respectively, and were validated to be diagnostic co-segregating markers for LrLC10. Our results both improve marker-assisted selection and help with the map-based cloning of LrLC10.